Influence of the mesh geometry evolution on gearbox dynamics during its maintenance - Dąbrowski, Zbigniew; Dziurdź, Jacek; Klekot, Grzegorz (Zielona Góra: Uniwersytet Zielonogórski)
Toothed gears constitute the necessary elements of power transmission systems. They are applied as stationary devices in drive systems of road vehicles, ships and crafts as well as airplanes and helicopters. One of the problems related to the toothed gears usage is the determination of their technical state or its evolutions.
Keywords: geometry of gears; slippage velocity; vibroacoustics